Development of Lichen Planopilaris-Like Alopecia following Occupational Exposure to Trichloroethylene and Tetrachloroethylene - Marks, Dustin H. (Skin Appendage Disord, 2019)
BACKGROUND: We report a case of acute and severe lichen planopilaris (LPP)-like alopecia in a 35-year-old male construction worker following occupational exposure to trichloroethylene (TCE) and tetrachloroethylene (PCE). CASE REPORT: Two weeks after initiating ground-intrusive construction at a previous dry-cleaning facility site, the patient developed sudden scalp pruritus and associated patchy hair loss. As subsequent scalp biopsies revealed LPP, he was started on hydroxychloroquine at 200 mg twice daily and clobetasol solution once daily. Despite treatment, the patient's hair loss rapidly progressed to involve >95% of his scalp within 3 years. An official “work clean” policy report revealed high-concentration exposure to TCE and PCE. CONCLUSION: Although causation cannot be proven, the close temporal relationship and rapid progression of LPP-like alopecia in an atypical patient demographic support a strong correlation between chemical exposure to TCE/PCE and scarring hair loss.